Counselling male sexual offenders: a strengths-focused approach - Smith, Andrew (Routledge, Taylor & Francis Group, 2018)
Introduction -- Shame, identity and lifestyle transitions -- Initial stage of the counselling process: the counselling contract -- Goal-setting -- Life story themes -- Life story themes: developing profiles -- Life story themes: counselling victims of abuse who have gone on to sexually offend -- Offence-focused interventions -- Psycho-educational interventions -- Facilitating victim empathy -- Fantasy management -- Applying strengths-focused interventions to safety planning